Construction of Cu2O/Cu heterojunction with hierarchical hollow sphere structure as visible-light driven photocatalyst for efficient water remediation. Issue 3 (June 2022) - Li, Junhua; Huang, Linsen; Yang, Zhimei; Liu, Zengjian; Sun, Xiaosong
Abstract: Sunlight driven photocatalytic degradation is an effective and eco-friendly technology for water remediation. And formation of metal-semiconductor heterojunction provides a promising strategy to enhance the photocatalytic efficiency of photocatalyst. In this work, the hierarchical Cu2 O/Cu hollow sphere was newly prepared by a simple template-free and one-pot solvothermal method without using any organic capping agents. The composition, morphology structure and photoelectric properties of the prepared photocatalysts were investigated by the characterization of XRD, XPS, SEM, TEM, nitrogen adsorption/desorption isotherms, UV-DRS and EIS, etc. It was found that the Cu2 O/Cu composite with hierarchical hollow sphere structure exhibits good stability and excellent photocatalytic activity for the degradation of methyl orange (MO) and tetracycline (TC) under visible light, because the huge specific surface area provides more active sites and the Cu2 O/Cu heterojunction could efficiently facilitate photogenerated carries separation. Further, free radical scavenging experiments and EPR tests confirmed the ·O2 - radicals were produced and played the most important role in the photocatalytic process. Finally, the possible photocatalytic mechanism and the transfer processes of photogenerated carriers of hierarchical Cu2 O/Cu hollow sphere was proposed. As a result, the hierarchical Cu2 O/Cu hollow sphere may be a suitable candidate of high-efficiency photocatalyst for the wastewater treatment. Graphical Abstract: ga1 Highlights: The hierarchical Cu2 O/Cu hollow sphere is synthesized by a template-free and one-plot solvothermal method. The hierarchical Cu2 O/Cu hollow sphere exhibits excellent photocatalytic performance for MO and TC under visible light. The possible photocatalytic mechanism and the transfer processes of photogenerated carriers is proposed.